INFLUENCE OF COMPONENTS OF METABOLIC SYNDROME ON THE PATIENTS’ LIFE QUALITY - N. S. Alekseyeva (Acta Biomedica Scientifica, 2014)
We researched the influence of components of metabolic syndrome on the indices of patients' life quality. Patients with abdominal obesity and different combination of components of metabolic syndrome were studied. The assessment of indices of life quality was conducted using MOS SF-36 enquirer. It was found that each component of metabolic syndrome might decrease indices of physical and mental health. In case of long existence of single components of metabolic syndrome the combination of most of them and aggravation of physical activity, emotional state, general and mental health.